Efficacy and safety of bevacizumab for the treatment of glioblastoma - YU, ZHIYUN (Exp Ther Med, 2016)
Glioblastoma (GBM) is the most common and devastating primary malignant intracranial tumor in adults. The current first-line treatment for patients with newly diagnosed GBM is surgical resection followed by radiotherapy plus concomitant and adjuvant temozolomide. This treatment protocol may prolong the survival period of the patient, however it is not curative and more effective therapeutic strategies are required. GBM is a type of highly vascularized tumor with increased expression levels of vascular endothelial growth factor (VEGF), which is a significant mediator of angiogenesis. Since angiogenesis is essential for tumor growth, anti-angiogenic therapies hold potential for the treatment of GBM, and targeting VEGF has demonstrated promising results in previous studies. Bevacizumab (BEV) is a recombinant humanized monoclonal antibody that inhibits VEGF and is approved by the US Food and Drug Administration as a monotherapy treatment for patients with recurrent GBM and is associated with manageable toxicity. Previous studies have demonstrated that BEV may be an effective treatment for recurrent GBM, with prolonged progression-free survival and overall survival, and maintained patient quality of life and functional status. The present review article briefly outlines the mechanism of action of BEV and summarizes the current literature and clinical trial research on the role of BEV for the treatment of patients with recurrent and newly diagnosed GBM.